On the Costa Rican Word “Sácalas”: Origin, Meaning and Vitality - Jara Murillo, Carla Victoria (2020)
In this paper three aspects of the Costa Rican word sácalas are addressed, namely, the origin that is recorded in lexicographical works; the semantic dichotomy that is reflected between two basic meanings: 'flattering' and 'intrusive', and finally, by means of a search of concordances by internet, its frequency and its contexts of appearance.